Mission and money : Christian mission in the context of global inequalities - Auvinen-Pöntinen, Mari-Anna.; Jørgensen, Jonas Adelin. (Theology and Mission in World Christianity, 2016)
Mission and Money; Christian Mission in the Context of Global Inequalities offers academic discussion about the mission of the Church in the context of contemporary economic inequalities globally, challenging the reader to reconsider mission in the light of existing poverty, and investigating how economic structures could be challenged in the light of ethical and spiritual considerations. The book includes contributions on the subjects of poverty and inequality from the theologians, economists and anthropologists who gave keynote presentations at the European Missiological Conference (IAMS Europe) that took place in April 2014 in Helsinki, Finland. This conference was a major step forward in terms of discussion between missiologists and economists on global economic structures and their influence on human dignity. Contributors are: Mari-Anna Auvinen-Pöntinen, Stephen B. Bevans, Jonathan J. Bonk, Ulrich Duchrow, Jonas Adelin Jørgensen, Vesa Kanniainen, Veli-Matti Kärkkäinen, Tinyiko Sam Maluleke, Gerrie Ter Haar, Evi Voulgaraki-Pissina, Mika Vähäkangas, Felix Wilfred.